A Comparative study for Diagnosis of initial caries using Laser Fluorescence Techniques, DIAGNOdent and Conventional Methods - Abdalla Abdalla, Hassan; Abraheem Mohammed Salih, Samiyah (Libyan Journal of Public Health Practices, 2025)
Timely detection of dental caries, including early enamel lesions and advanced dentinal involvement, is essential for effective clinical management. This in vivo investigation assessed the diagnostic accuracy of conventional and fluorescence-based adjuncts across proximal, occlusal, and noncavitated facial smooth-surface lesions. A cohort of 195 patients (aged 8–40 years) underwent visual inspection, tactile probing, bitewing radiography, and evaluations using light-emitting diode (LED) fluorescence, laser-induced fluorescence, and the DIAGNOdent system. DIAGNOdent measurements were interpreted using both manufacturer-defined cutoffs and newly calibrated thresholds. Data were analyzed via receiver operating characteristic (ROC) curve analysis and chi-square tests, with significance at p < 0.001. ROC analysis yielded AUC values > 0.85 for fluorescence modalities, indicating robust discriminative performance. Bitewing radiography demonstrated exceptional specificity—up to 99%—for identifying sound surfaces, corroborating findings in fluorescence studies of occlusal caries detection. DIAGNOdent showed superior sensitivity for enamel caries, with sensitivity approximating 85% using manufacturer cutoffs and 81% with revised thresholds, paralleling reported performance in vivo. Diagnostic accuracy for dentinal lesions was comparable between DIAGNOdent and traditional methods. Specifically, for noncavitated facial smooth-surface lesions, DIAGNOdent achieved over 84% overall accuracy, with sensitivity of 87.6% and specificity of 96.9%. Interobserver agreement across modalities was moderate to high (κ = 0.33–0.75), indicating reproducibility consistent with prior DIAGNOdent pen evaluations. Integration of visual inspection with fluorescence-based methods further enhanced diagnostic metrics, underscoring the value of adjunctive fluorescence devices. Overall, advanced fluorescence-based diagnostics—particularly DIAGNOdent—offer increased sensitivity and high specificity, supporting their clinical utility in early caries detection and timely intervention